18F-labeled FGFR1 peptide: a new PET probe for subtype FGFR1 receptor imaging - Chen, Yang; Han, Jingya; Zhao, Yan; Zhao, Xinming; Zhao, Mengmeng; Zhang, Jingmian; Wang, Jianfang (Frontiers in Oncology, 2023)
The fibroblast growth factor receptor (FGFR) family is highly expressed in a variety of tumor types and represents a new target for cancer therapy. Different FGFR subtype aberrations have been found to exhibit highly variable sensitivity and efficacy to FGFR inhibitors. The present study is the first to suggest an imaging method for assessing FGFR1 expression. The FGFR1-targeting peptide NOTA-(PEG2)-KAEWKSLGEEAWHSK was synthesized by manual solid-phase peptide synthesis and high-pressure liquid chromatography (HPLC) purification and then labeled with fluorine-18 using NOTA as a chelator. In vitro and in vivo experiments were conducted to evaluate the stability, affinity and specificity of the probe. Tumor targeting efficacy and biodistribution were evaluated by micro-PET/CT imaging in RT-112, A549, SNU-16 and Calu-3 xenografts. The radiochemical purity of [18F]F-FGFR1 was 98.66% ± 0.30% (n = 3) with excellent stability. The cellular uptake rate of [18F]F-FGFR1 in the RT-112 cell line (FGFR1 overexpression) was higher than that in the other cell lines and could be blocked by the presence of excess unlabeled FGFR1 peptide. Micro-PET/CT imaging revealed a significant concentration of [18F]F-FGFR1 in RT-112 xenografts with no or very low uptake in nontargeted organs and tissues, which demonstrated that [18F]F-FGFR1 was selectively taken up by FGFR1-positive tumors. [18F]F-FGFR1 showed high stability, affinity, specificity and good imaging capacity for FGFR1-overexpressing tumors in vivo, which provides new application potential in the visualization of FGFR1 expression in solid tumors.